2015
DOI: 10.1152/japplphysiol.00387.2014
|View full text |Cite
|
Sign up to set email alerts
|

Downhill running and exercise in hot environments increase leukocyte Hsp72 (HSPA1A) and Hsp90α (HSPC1) gene transcripts

Abstract: Stressors within humans and other species activate Hsp72 and Hsp90α mRNA transcription, although it is unclear which environmental temperature or treadmill gradient induces the largest increase. To determine the optimal stressor for priming the Hsp system, physically active but not heat-acclimated participants (19.8 ± 1.9 and 20.9 ± 3.6 yr) exercised at lactate threshold in either temperate (20°C, 50% relative humidity; RH) or hot (30°C, 50% RH) environmental conditions. Within each condition, participants com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 63 publications
8
18
0
Order By: Relevance
“…Previous work from our research group has demonstrated that the leukocyte Hsp72 and Hsp90α mRNA responses are larger following exercise in hot compared to temperate environments (Gibson et al, 2015c, 2016), and following downhill compared to flat running (Tuttle et al, 2015). It is known that downhill running is an effective whole body preconditioning strategy (Shima et al, 2008; Touchberry et al, 2012; Isanejad et al, 2015), consequently, an acute preconditioning trial featuring both stressors (hot environmental conditions and downhill running; hot downhill running) was selected in the current experimental design to maximize stimuli to initiate the HSR and subsequent cellular preconditioning.…”
Section: Methodsmentioning
confidence: 80%
See 4 more Smart Citations
“…Previous work from our research group has demonstrated that the leukocyte Hsp72 and Hsp90α mRNA responses are larger following exercise in hot compared to temperate environments (Gibson et al, 2015c, 2016), and following downhill compared to flat running (Tuttle et al, 2015). It is known that downhill running is an effective whole body preconditioning strategy (Shima et al, 2008; Touchberry et al, 2012; Isanejad et al, 2015), consequently, an acute preconditioning trial featuring both stressors (hot environmental conditions and downhill running; hot downhill running) was selected in the current experimental design to maximize stimuli to initiate the HSR and subsequent cellular preconditioning.…”
Section: Methodsmentioning
confidence: 80%
“…It is known that downhill running is an effective whole body preconditioning strategy (Shima et al, 2008; Touchberry et al, 2012; Isanejad et al, 2015), consequently, an acute preconditioning trial featuring both stressors (hot environmental conditions and downhill running; hot downhill running) was selected in the current experimental design to maximize stimuli to initiate the HSR and subsequent cellular preconditioning. This was compared to a temperate flat trial (flat running in a temperate environment) where no change in leukocyte Hsp72 and Hsp90α mRNA has been previously observed (Tuttle et al, 2015) and thus no preconditioning effect was hypothesized to occur. A 7 d period between trials was selected to ensure any spontaneous preconditioning effect from exercise stress on core temperature (Barnett and Maughan, 1993) and leukocyte HSP72 (Fehrenbach et al, 2001; Lee et al, 2014), had returned to baseline following TPC1 TEMPFLAT .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations